Los límites de la ΓΡΑΦΗ ΑΜΒΛΩΣΕΩΣ: la (i)licitud del aborto en el derecho ateniense (Argos, 2025)
Our study takes as a starting point the contradictions on evidence concerning the use of abortive measures in Classical Greek society, transmitted not only through medical treatises (such as the corpus hippocraticum) but also through philosophical works (Plato, Aristotle). Based on this theoretical dispute, the necessity of analyzing the legality or illegality of abortion within the provisions of Athenian Law is concluded. A strict examination of lexical elements in the two fragments that constitute Lysias' speech X (Gernet's edition), which stands as the only legal remain on the apparent criminalization of ἄμβλωσις, allows us to suggest a number of inferences on the judicial interpretation of the facts alleged and on the characteristics of its treatment within court proceedings in the late Vth and early IVth Century.
Keywords: abortion; athenian law; Lysias; woman; graphé amblóseos